Educational video on animal welfare at the slaughterhouse in East Africa - Falzon, Laura C. (Zoonotic and Emerging Diseases Research Team, 2019)
Learn about how you can play your part improving animal welfare at the slaughterhouse in East Africa. This video was created primarily for a Kenyan audience, funded by a UK BBSRC/GCRF Public Engagement grant implemented by Laura Falzon who is part of the Zoonotic and Emerging Diseases Group, which is based jointly between the University of Liverpool (UK) and the International Livestock Research Institute (Kenya). The work is also supported by the CGIAR Agriculture for Nutrition and Health Program.